Immunological repertoire linked to PSTPIP1-associated myeloid-related inflammatory (PAMI) syndrome - Leonardo Oliveira Mendonça; Maria Teresa Terreri; Fabiane Mitie Osaku; Samar Freschi Barros; Karen Francine Köhler; Alex Isidoro Prado; Myrthes Toledo Barros; Jorge Kalil; Fabio Fernandes Morato Castro (BMC, 2021)
Abstract Background Mutations along PSTPIP1 gene are associated to two specific conditions, PAPA syndrome and PAMI syndrome, both autoinflammatory disorders associated to disturbances in cytoskeleton formation. Immunological aspects of PAMI syndrome has not yet been reported neither the clinical impact on therapeutical decisions. Methods Clinical data of patients records were retrospectively accessed. Genomic DNA were extracted and sequenced following standard procedures. Peripheral lymphocytes were quantified in T, B e FOXP3 phenotypes. Results We describe two related patients with PAMI syndrome harboring the usual E250K mutation. Anti-IL1 therapy could partially control the disease in the index patient. A broad spectrum of immunological effects as well as an aberrant expression of FOXP3 could be observed. Conclusions Here we report two related brazilian patients with PAMI syndromes harboring the E250K mutation in PSTPIP1, their immunological aspects and the therapeutical response to canakinumab.